Fostering Skills in Cameroon : Inclusive Workforce Development, Competitiveness, and Growth - Sosale, Shobhana (Washington, DC: World Bank, 2016)
This report reaches conclusions and offers policy recommendations to answer these questions: What has been the trajectory of Cameroon’s economic growth? Which sectors have contributed to growth? What jobs are being created? What types of skills are being used in the sectors where the highest percentages of the population are employed? What are the demand and supply barriers to skills? Which policies and institutions are in play? Are they sufficient? What needs to or could be reformed? Cameroon has good prospects for moving to middle-income status. It can create a more dynamic, responsive workforce. But a new strategy is required. It can be done.This report proposes new directions and provides recommendations.